The complete chloroplast genome of monocot plant, Maianthemum dilatatum - Raman Gurusamy; Eun Mi Lee; Gi Heum Nam; Byoungyoon Lee; SeonJoo Park (Mitochondrial DNA. Part B. Resources, 2018)
The complete chloroplast genome sequence of Maianthemum dilatatum is sequenced and analyzed. The chloroplast genome is 156,921 bp, with 36.7% GC content. A pair of inverted repeats of 26,468 bp is separated by a large single-copy region (85,554 bp) and a small single-copy region (18,431 bp). It encodes 86 protein-coding genes, 38 tRNA genes and 8 rRNA genes. Of 132 individual genes, 19 genes are duplicated in the IR regions, while 14 genes are encoded with one intron and three genes with two introns.